Frequency selective surfaces on flexible thin plastic substrates - N. A. F. M. Zainudin; S.N. Azemi; M.F. Jamlos; A.A. Al-Hadi; P.J. Soh (Institute of Advanced Engineering and Science, 2019)
The capability of the flexible substrate of the frequency selective surface (FSS) to filter out particular frequency is discussed in this paper. A new type of FSS are applied using flexible thin plastic substrate to enhance the performance of the conventional FSS that lacks of flexibility and cannot be used in bending surface. A simulation based investigation shows that the diameter or length of the square has a significant effect on the band-stop selective characteristic of the FSS. The frequency response of the band-stop are at 2.45GHz that drop at -10dB.